2005
DOI: 10.1021/ja040226s
|View full text |Cite
|
Sign up to set email alerts
|

Silver(I)−Imidazole Cyclophane gem-Diol Complexes Encapsulated by Electrospun Tecophilic Nanofibers:  Formation of Nanosilver Particles and Antimicrobial Activity

Abstract: Silver(I)-imidazole cyclophane gem-diol complex, 3 [Ag2C36 N10(O)4](2+)2(x)-, where x = OH- or CO3(2-), was synthesized and well characterized. The minimum inhibition concentration tests showed that the aqueous form of 3 is 2 times less effective as an antibiotic than 0.5% AgNO3, with about the same amount of silver. The antimicrobial activity of 3 was enhanced when encapsulated into Tecophilic polymer by electrospinning to obtain mats made of nano-fibers. The fiber mats released nanosilver particles, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
324
2
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 540 publications
(339 citation statements)
references
References 26 publications
4
324
2
9
Order By: Relevance
“…It has been shown that silver nanoparticles prepared with a variety of synthetic methods have effective antimicrobial activity (Lok et al 2006;Baker et al 2005;Aymonier et al 2002;Melaiye et al 2005;Sondi and Salopek-Sondi 2004;Kim et al 2008;Lee et al 2008;Alt et al 2004). In the present study, the silver nanoparticles were prepared by chemical reduction method to assess the antibacterial activity.…”
Section: Proteus Morganii Staphylococcus Aureusmentioning
confidence: 87%
“…It has been shown that silver nanoparticles prepared with a variety of synthetic methods have effective antimicrobial activity (Lok et al 2006;Baker et al 2005;Aymonier et al 2002;Melaiye et al 2005;Sondi and Salopek-Sondi 2004;Kim et al 2008;Lee et al 2008;Alt et al 2004). In the present study, the silver nanoparticles were prepared by chemical reduction method to assess the antibacterial activity.…”
Section: Proteus Morganii Staphylococcus Aureusmentioning
confidence: 87%
“…7 This issue 80 has been successfully resolved by using biologically relevant imidazole-containing molecules as NHC sources. An outstanding candidate is caffeine, a prevalent xanthine that is readily available, cheap, and of lower toxicity even when alkylated (LD 50 ~1.0 g kg -1 ).…”
mentioning
confidence: 99%
“…A toxicity of minimum level is denoted when HL-60 cell grown on metal silver plate. Some researchers did accumulation of nano silver on cells experiment [7][8][9][10][11] and denoted that maximum accumulation can be cytotoxic in rat liver cell and Mammalian germ line stem cells [12].…”
Section: Introductionmentioning
confidence: 99%